Soft x-ray free electron laser microfocus for exploring matter under extreme conditions. - Nelson, A; Toleikis, S; Chapman, H; Bajt, S; Krzywinski, J; Chalupsky, J; Juha, L; Cihelka, J; Hajkova, V; Vysin, L; Burian, T; Kozlova, M; et al. (Optical Society of American (OSA), 2009)
We have focused a beam (BL3) of FLASH (Free-electron LASer in Hamburg: lambda = 13.5 nm, pulse length 15 fs, pulse energy 10-40 microJ, 5 Hz) using a fine polished off-axis parabola having a focal length of 270 mm and coated with a Mo/Si multilayer with an initial reflectivity of 67% at 13.5 nm. The OAP was mounted and aligned with a picomotor controlled six-axis gimbal. Beam imprints on poly(methyl methacrylate) - PMMA were used to measure focus and the focused beam was used to create isochoric heating of various slab targets. Results show the focal spot has a diameter of < or =1 microm. Observations were correlated with simulations of best focus to provide further relevant information.